Hubungan antara Kadar Hemoglobin Ibu Hamil Trimester III dengan Berat Badan Janin di Puskesmas Trauma Center Samarinda - Tri Wahyuni; Rina Ayu Hanna (Universitas Muhammadiyah Kalimantan Timur, 2017)
Background: Hemoglobin is a widely used parameter to define the prevalence of anemia. Anemia in pregnant women will increase the risk of getting Infant Low Birth Weight (LBW), the risk of bleeding before and during delivery will even cause the death of the mother and baby if the mother is suffering from severe anemia. World Health Organization (WHO) recommends pregnant women ideal Hemoglobin levels were more than 11 g / dl. High and low levels of hemoglobin of pregnant women during pregnancy has an effect on birth weight because it can lead to impaired fetal growth in the womb.Objective: This study aimed to determine the relationship of the levels of Hemoglobin third trimester pregnant women with fetal weight in PHC Trauma Center Samarinda.Methods: This study is a descriptive correlationalapproach to time series. The study population was selurus third trimester pregnant women were recorded and checkups in Health Center Trauma Center corresponding inclusion criteria starting from the month of May to July 2017. The sample in this study with amethod total sampling with a total sample of 39 people. Instrument research using observation sheet. The collected data were analyzed by using univariate analysis (median and frequency distribution) and bivariate analysis techniques withtest. chi squareResults: It was found that there was a significant correlation between hemoglobin level third trimester pregnant women with fetal weight in PHC Trauma Center with P-value = 0.000.Conclusion: respondent characteristics in Puskeamas Trauma Center study that most of the respondents were in the age group 20-35 years as many as 33 people (84.6%) are mostly high school-educated respondents as many as 19 people (48.7%), most respondents were housewives as many as 26 people (66.7%), most respondents second pregnancy or more (multigravida) as many as 23 people (59.0%), most of the respondents had higher levels of hemoglobin to normal as many as 24 people (61.5%) and the majority of respondents have a baby of normal weight 21 persons (53.8%). There is a relationship Hemoglobin levels of third trimester pregnant women with fetal weight in PHC Trauma Center samarinda with P-value = 0,000 in obtaining the value of OR = 70,000.